2022
DOI: 10.1021/acs.jcim.1c01557
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Inhibitors of HDAC1–3 Enzymes Aided by In Silico Design Strategies

Abstract: Histone deacetylases (HDACs) are overexpressed in cancer, and their inhibition shows promising results in cancer therapy. In particular, selective class I HDAC inhibitors such as entinostat are proposed to be more beneficial in breast cancer treatment. Computational drug design is an inevitable part of today's drug discovery projects because of its unequivocal role in saving time and cost. Using three HDAC inhibitors trichostatin, vorinostat, and entinostat as template structures and a diverse fragment library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Frontiers in Chemistry frontiersin.org polymerization inhibitor (Dwivedi et al, 2022), PARP-1 inhibitor 2 (Syam et al, 2022), CDK2 inhibitor 3 (Qayed et al, 2022), HDAC-1-3 inhibitor 4 (Cheshmazar et al, 2022), VEGFR-2 inhibitor 5 (Taghour et al, 2022) were identified for cancer therapies. Furthermore, AChE inhibitor 6 (Macedo Vaz et al, 2022) for treatment of Alzheimer's disease and Mtb RNAP inhibitor 7 (Mekonnen Sanka et al, 2022) for antitubercular and antimicrobial treatment were deserve further study.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Frontiers in Chemistry frontiersin.org polymerization inhibitor (Dwivedi et al, 2022), PARP-1 inhibitor 2 (Syam et al, 2022), CDK2 inhibitor 3 (Qayed et al, 2022), HDAC-1-3 inhibitor 4 (Cheshmazar et al, 2022), VEGFR-2 inhibitor 5 (Taghour et al, 2022) were identified for cancer therapies. Furthermore, AChE inhibitor 6 (Macedo Vaz et al, 2022) for treatment of Alzheimer's disease and Mtb RNAP inhibitor 7 (Mekonnen Sanka et al, 2022) for antitubercular and antimicrobial treatment were deserve further study.…”
Section: Figurementioning
confidence: 99%
“…To effectively and efficiently design and develop new drugs, computational methods had been applied for drug design including target identification, seeking out and optimizing lead compounds prediction of pharmacokinetic and toxicological properties as well as compound synthesis by molecular docking and molecular dynamics, virtual screening, pharmacophore and ADMET prediction. Novel quinazoline derivative 1 as tubulin polymerization inhibitor ( Dwivedi et al, 2022 ), PARP-1 inhibitor 2 ( Syam et al, 2022 ), CDK2 inhibitor 3 ( Qayed et al, 2022 ), HDAC-1-3 inhibitor 4 ( Cheshmazar et al, 2022 ), VEGFR-2 inhibitor 5 ( Taghour et al, 2022 ) were identified for cancer therapies. Furthermore, AChE inhibitor 6 ( Macedo Vaz et al, 2022 ) for treatment of Alzheimer’s disease and Mtb RNAP inhibitor 7 ( Mekonnen Sanka et al, 2022 ) for antitubercular and antimicrobial treatment were deserve further study.…”
Section: Computational Chemistry In Drug Discoverymentioning
confidence: 99%
“…With the exception of 2, 3, 8, 9, 11, and 13, the remaining compounds are known and reported elsewhere for different applications [24][25][26][27][28][29][30][31][32][33][34][35]. Nonetheless, all 20 compounds were conveniently synthesized in two steps by amidation reactions.…”
Section: Synthesismentioning
confidence: 99%